P-188 A partnership approach to end of life care discharges. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Longmore, Chloe; Penny, Jane; Jones, Penny
Abstract : Getting patients from acute hospitals into the community at the end of life is difficult. The problems include: Patients and carers having a poor experience at the end of life Complaints to the acute trust Patients not achieving their preferred care setting or place of death Beds being blocked in the acute trust. The problem is caused by: The complexity of discharging a patient at the end of life Lack of rapid access to care in the community. Getting care right at the end of life is of paramount importance. There is only one chance to get it right and meeting preferred place of care can be very important to a patient and carers. A pilot project between an acute trust, hospice and charity has been in operation since January 2015 and works in two ways: A new role was created in the trust, discharge liaison practitioners, to identify patients at the end of life and case manage their discharge to their preferred place of care The charity and hospice partners collaborated to provide a team of HCAs in the community rapidly available to support patients with short packages of care until statutory services are able to take over. The project objectives include: Improving the experience of patients at the end-of-life Increasing the percentage of patients achieving their preferred place of care and death Reducing discharge delays at the end-of-life Saving bed days for the acute trust. The project has supported over 500 patients and is currently being evaluated by the charity partner with results due in September 2016. The project partners will then determine the project future based on the learning from this evaluation. This has national and regional implications as this model could be replicated in any region in the UK.